Effectiveness of game-based freestyle swimming training models for early children (4-6 years) - Doni Douglas Tambunan; Sukiri; Nofi Marlina Siregar (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2023)
The aim of this study was to obtain empirical data about the effectiveness and results of a game-based freestyle swimming training model for early childhood (4-6 years). This type of research is an experiment with a pre-test and post-test design. Data analysis techniques collect effectiveness test data using the T test with SPSS software. The effectiveness test was carried out in early childhood (4-6 years) at Flobamora Swimming Club in Senen, Central Jakarta with a total of 14 children as subjects who were given treatment using a variety of game-based freestyle swimming training models for 16 meetings. The freestyle swimming motion assessment instrument is carried out by the freestyle swimming test. The results of the study, in the experimental group, the mean pre-test was 8,428 and the mean post-test was 12. Meanwhile, in the control group, the pre-test was 6.5 and the post-test was 8.2. Testing the success of the experimental method with the control, the results obtained are sig 0.000 <0.05, which means that there is a significant difference between the subjects who were given control treatment and the experiment, with a difference of 3.80 so that it can be said that the experimental method that has been applied provides better effectiveness than with control group.